A CEBOCEPHALUS (CYCLOPIA) MONSTER IN A CROSS-BRED COW - KHASATIYA, C T (The Indian Journal of Animal Reproduction, 2010)
A cebocephalus / cyclopia monster with epitheliogenesis imperfecta over the forehead and body, having rudimentary and separate eye balls and atypical deformed ears and jaw was delivered by traction in an HF crossbred cow.